ECOSYTEM KEWIRAUSAHAAN DAN DAMPAKNYA PADA MINAT BERWIRAUSAHA - Kholid Mawardi, Mukhammad (FIA UB, 2020)
One of the leverage of a country's competitiveness is the level of entrepreneurship. Universities are one of the institutions that contribute to the development of entrepreneurship, but there has been no consistent research results on how Universitiy can boost entrepreneurship. The creation of entrepreneurship ecosystem is one of the manifestation of Universities’ roles in improving entrepreneurship. Recent research involving 214 students in the Business Administration of Universitas Brawijaya aims to analysis the effects of entrepreneurship ecosystem on the entrepreneurial interest of students. By using multiple liner regression analysis, it was found that there is a simultaneous significant effect of all the variables of entrepreneurship ecosystem; cultural variable, material variable and social variable on entrepreneurship interest and partially, only the cultural variable (X1) and variable material (X3) that have a significant influence on the intention of entrepreneurial (Y) and the not significan between the social variables (X2) and intention entrepreneurial (Y).